Rembrandt's reading : the artist's bookshelf of ancient poetry and history - Golahny, Amy (Rembrandt, 2010)
Acknowledgments -- Preface: The Scope of the Study -- Book Culture -- Rembrandt's Training -- Rembrandt's Bookshelf, Part I -- Rembrandt's Bookshelf, Part II: "15 books in various sizes" Rembrandt's Bookshelf, Part III: German Folios -- Rembrandt's Later Imagery: After the 1656 Inventory -- Artists' Libraries: Practicality and Universality -- Notes -- Bibliography -- Illustration Acknowledgments -- Index